2016
DOI: 10.1371/journal.pone.0161635
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Bifidobacterium on Intestinal Barrier Function in LPS-Induced Enterocyte Barrier Injury of Caco-2 Monolayers and in a Rat NEC Model

Abstract: Zonulin protein is a newly discovered modulator which modulates the permeability of the intestinal epithelial barrier by disassembling intercellular tight junctions (TJ). Disruption of TJ is associated with neonatal necrotizing enterocolitis (NEC). It has been shown bifidobacterium could protect the intestinal barrier function and prophylactical administration of bifidobacterium has beneficial effects in NEC patients and animals. However, it is still unknown whether the zonulin is involved in the gut barrier d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 41 publications
(55 reference statements)
6
134
0
3
Order By: Relevance
“…Although the mucus layer may impact direct Bifidobacterium -IEC interactions, previous studies have indicated that B. breve UCC2003 surface molecules, such as EPS and the Tad pilus may modulate IEC function via signaling through TLRs [17, 49]. Moreover, bifidobacterial metabolites, such as short-chain fatty acids may also act to modulate the IEC transcriptome, with previous studies indicating enhanced expression of TJs and cadherins via acetate [9, 14, 50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mucus layer may impact direct Bifidobacterium -IEC interactions, previous studies have indicated that B. breve UCC2003 surface molecules, such as EPS and the Tad pilus may modulate IEC function via signaling through TLRs [17, 49]. Moreover, bifidobacterial metabolites, such as short-chain fatty acids may also act to modulate the IEC transcriptome, with previous studies indicating enhanced expression of TJs and cadherins via acetate [9, 14, 50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Some natural substances that have shown such improvement include quercetin, butyrate, L-glutamine, and the probiotic Bifidobacterium, and the lignite extract compound studied herein [19,[22][23][24][25][26][27][28][29][30][31][32]. Larazotide, a synthetic pharmaceutical and zonulininhibitor, has also shown to improve tight junction formation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Transepithelial electrical resistance (TEER) is widely accepted as an indicator of tight junction permeability [17][18][19][20]. TEER was measured in both IEC-6 and Caco-2 cells seeded in 24-well transwell plates (1-micron pore size, Becton Dickinson).…”
Section: Transepithelial Electrical Resistancementioning
confidence: 99%
“…emphasise the importance of the species and even the strain of Bifidobacterium that is used. In a necrotising enterocolitis (NEC, which is also linked to epithelial barrier disruption) mouse model, B. breve was shown to up-regulate TJ proteins Claudin 4 and Occludin [51], and a non-specified species of Bifidobacterium increased ZO-1 in a rat NEC model [8]. Studies have also shown that the effects of bifidobacteria are only exerted, or are increased, when live bifidobacteria are used.…”
Section: Epithelial Cellsmentioning
confidence: 99%
“…Bifidobacteria have been used for many years as supplements to promote host wellbeing, as their presence, including the high levels observed in infants and stable levels in adults, is associated with a 'healthy' state. These bacteria are particularly effective at protecting against infectious diseases [4][5][6][7] and modulating immune responses [7,8]. This review discusses Bifidobacterium across the life course, and focuses on species and specific strains that have been studied in the context of immune modulation and treatment of disease.…”
Section: Introductionmentioning
confidence: 99%